(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
This Article Seeks To Read The Reception Of (Islamic Literature) In Modern Arab Criticism, In A Comparative View Of The Theses Of Muhammad Iqbal Alaraui, One Of The Most Interested In This Literary Trend; In The Second Half Of Last Century, The Authors Of This Literature Published A Large Number Of Creative And Critical Texts That Could Provoke Much Debate And Discussion. Arawi’s Arguments Continued To Form A Critical And Theoretical Phenomenon. What Is The Position Of The Term (Islamic Literature) Of Dualism: Rejection And Acceptance? Throughout His Historic Procession? What Are The Arguments Of Alaraui And Those Who Have The Same Opinion Of Contemporary Critics? Key Words- Islamic Literature - Concept - Rooting – Alarawi.